A Geographically Widespread Outbreak Investigation and Development of a Rapid Screening Method Using Whole Genome Sequences of Enterohemorrhagic Escherichia coli O121 - Lee, Ken-ichi; Morita-Ishihara, Tomoko; Iyoda, Sunao; Ogura, Yoshitoshi; Hayashi, Tetsuya; Sekizuka, Tsuyoshi; Kuroda, Makoto; Ohnishi, Makoto; , EHEC Working Group in Japan; Takenuma, Hiroko; Seto, Junji; Suzuki, Yu; et al. (Frontiers in Microbiology, 2017)
From 2014 to 2015, we investigated a suspected nationwide outbreak of enterohemorrhagic Escherichia coli serogroup O121. However, similar pulsed field gel electrophoresis (PFGE) profiles and the lack of epidemiological links between the isolates made detection of the outbreak difficult. To elucidate a more precise genetic distance among the isolates, whole genome sequence (WGS) analyses were implemented in the investigation. The WGS-based single nucleotide polymorphism (SNP) analysis showed that 23 out of 44 isolates formed a distinct cluster (the number of intra-cluster SNPs was ≤ 8). Specific genomic regions in the clustered isolates were used to develop a specific PCR analysis. The PCR analysis detected all the clustered isolates and was suitable for rapid screening during the outbreak investigation. Our results showed that WGS analyses were useful for the detection of a geographically widespread outbreak, especially for isolates showing similar PFGE profiles and for the development of a rapid and cost-effective screening method.